Education Policies and Practices for Basic and Primary Education Development in Nepal - Acharya, Bisna (Molung Educational Frontier, 2019)
Education policies are considered as the strategic link between the education's vision and day-to-day operations of education system of a nation. The comprehensive education policies allow to the decision makers and employees to understand their role and responsibilities within predefined limits. Education policies allow management to guide operations without constant management intervention. Education policies in Nepal have been considered as a predetermined course of action which is established to provide a guide toward accepted strategies and objectives. These policies identify the key activities and provide a general strategy to decision-makers on how to handle issues as they arise. Policies also help to eliminate the common misunderstandings by identifying job responsibilities and establishing boundaries for the job holders. The present study deals with the issues regarding Education Policy Practice focusing on development of basic and primary education in Nepal. Therefore, the major concern of the study is to examine the development of basic and primary education in Nepal.